Investigation of Non-Linear Adaptive Responses and Split Dose Recovery Induced by Ionizing Radiation in Three Human Epithelial Derived Cell Lines - Lorna A. Ryan; Colin B. Seymour; Carmel E. Mothersill (SAGE Publishing, 2009)
Two almost completely exclusive fields in radiobiology deal with splitting doses of radiation and comparing the effect to a similar total dose given in one exposure. In radiotherapy, dose "fractionation" is used to "spare" normal tissue and in the low dose field, the adaptive response is well documented as a phenomenon where a small "priming" dose administered before the larger "challenge" dose reduces the effect of the large dose. There have been very few studies where these fields overlap, thus it is not possible to ascertain whether common or distinct mechanisms underlie both phenomena but this is certainly an interesting question and relevant to our understanding of high and low dose radiobiology. This paper presents data for three human cell lines with varying p53 status and radiation responses, treated at a range of times between first and second dose and for 3 different first doses (0.1, 0.5 and 2Gy). The data show that time between doses is critical. Protective (adaptive) effects were seen in each cell line but most prominently in the malignant HT 29 cell line. Surprisingly none of the cell lines showed pronounced split dose recovery. This suggests different mechanisms may underlie the two phenomena.